Real time harmonics estimation of distorted power system signal. (February 2016) - Ray, Pravat Kumar; Puhan, Pratap Sekhar; Panda, Gayadhar
Abstract: Power system harmonics should be estimated properly for the maintenance of power quality. So, there is a need for development of more accurate and computationally efficient estimation technique. In this context, this paper presents a harmonics estimation technique using a Variable Leaky Least Mean Square algorithm. In this proposed method drifting of parameters is avoided using a leak adjustment method. To improve the rate of convergence, step size is also adapted in this method. Real time power system is also imitated using different cases through simulation, which enables the superiority of the proposed method over the other existing techniques. Studies made on experimental data, processed in arduino due microcontroller, also support its superiority.